Nivolumab‐induced sialadenitis. Issue 5 (15th April 2018) - Takahashi, Saeko; Chieko, Xu; Sakai, Tetsuya; Hirose, Shigemichi; Nakamura, Morio
Abstract : Nivolumab has been increasingly used for a range of malignancies, and a variety of immune‐related adverse events (irAEs) have been reported with its use. Nivolumab‐induced sialadenitis (inflammation of salivary glands) and xerostomia (dry mouth) have been reported to occur in 0.03% and 0.05% respectively, but there have been no case reports published about these side effects. Sialadenitis is not a life‐threatening irAEs, but xerostomia can become irreversible if not recognized and treated as it can otherwise lower quality of life and result in susceptibility to infection. Therefore, healthcare providers need to know about sialadenitis as one of the irAEs of Nivolumab. Thus, we present the first case of nivolumab‐induced sialadenitis. A 70‐year old man with pulmonary adenocarcinoma developed sialadenitis 4 months after initiating nivolumab. His serum amylase levels were elevated to 1373 IU/L, and a biopsy of his labial minor salivary glands showed severe lymphocytic inflammation with damage to the glands. His sialadenitis was improved by taking corticosteroids and by ceasing nivolumab. Abstract : We report the first case of Nivolumab induced sialadenitis.